Attitude and acceptance towards bahasa Melayu among the speakers in the state of Pahang - Zulkifley Hamid,; Mohd. Asyraf Zulkifley,; Muammar Ghaddafi Hanafiah, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
This study focuses on the speakers of bahasa Melayu in the east coast of the Peninsula or more specifically in the state of Pahang Darul Makmur. Six districts in Pahang have been chosen as the area of study namely Temerloh, Maran, Jerantut, Muadzam Shah, Kuala Lipis, and Kuantan. In this study, the attitude and view of the urban and rural communities towards the capability and commercial value of bahasa Melayu will be seen and compared, whether or not they have changed. A close look at the language attitude has been made, and sociolinguistic approach has been used as a theoretical frameworks. As many as 200 questionnaire forms had been distributed to respondents aged between 10 to 61 years old. Other than the questionnaires, the data was also obtained using the interview and the observation methods. Data was analyzed using SPSS. The findings indicate that the language attitude of the East Coast community varies according to the variables that have been determined. Language attitude based on age, religion, educational level and residential location have illustrated a significant difference. However, from the income level and marital status, the language attitude does not show significant difference. All in all, based on the tests of validity and reliability, the finding shows that the attitude and acceptance of bahasa Melayu in the Malay community residing in the East Coast has been very positive.